TINJAUAN SUSPEN, SURPRISE, DAN NILAI MORAL DALAM KISAH “CERITA TAK BERUJUNG” KARYA ABDUL AZIZ ABDUL MAJID - Alamsyah, Teuku; Taib, Rostina; Armia, Armia; Nurrahmah, Nurrahmah (Jurnal Dedikasi Pendidikan, 2022)
This study aims to describe suspense, surprise, and moral values in the story “Cerita Tak Berujung” by Abdul Aziz Abdul Majid (2002). The data source of this research is "Cerita Tak Berujung” in the book "Mendidik dengan Cerita" by Abdul Aziz Abdul Majid (2002) with the original title Al-Qissah fi al-Tarbiyah. Data collection is carried out in the form of reviewing theories or relevant research results and developing theories in accordance with the aspects of the study. Data analysis was carried out in the form of content analysis following steps (1) reading/studying the story of "Cerita Tak Berujung" in detail, (2) determining the part of the text of the story that contains suspense and surprise referring to the results of theoretical studies and relevant research findings regarding these two things, (3 ) determine the moral values contained in the story which are stated implicitly refer to the theory of values in literary works, (4) describe the data from the analysis, and (5) draw conclusions from the results of the analysis. The results showed (1) the suspense of the story has begun to be woven by the author when choosing the diction for the title of the story and so it can be found at the beginning, middle, and towards the end of the story, (3) the strongest suspense is found near the end of the story, (4) surprise is found at the beginning of the story, in the middle of the story and like the suspense, the strongest surprise is found towards the end of the story, and (5) the dominant moral values found are honesty, respect for others, patience, and keeping promises.